Impact of the revised haemodynamic definition on the diagnosis of pulmonary hypertension in patients with systemic sclerosis. Issue 2 (22nd August 2019) - Jaafar, Sara; Visovatti, Scott; Young, Amber; Huang, Suiyuan; Cronin, Paul; Vummidi, Dharshan; McLaughlin, Vallerie; Khanna, Dinesh
Introduction: Pulmonary arterial hypertension (PAH) is one of the leading causes of mortality in systemic sclerosis (SSc). We explored the impact of the updated haemodynamic definition of pulmonary hypertension (PH), as proposed by the 6th World Symposium on Pulmonary Hypertension. Methods: In this single-centre retrospective analysis, patients with SSc who had right heart catheterisation (RHC) were included. We compared the prior PH definition to the updated PH definition. The prior definition classified PH as mean pulmonary arterial pressure (mPAP) ≥25 mmHg and further divided into pre-capillary PH (PAH and PH due to lung disease and/or hypoxia), post-capillary PH, and combined pre- and post-capillary PH groups. For the updated definition, PH was classified as mPAP >20 mmHg and further divided into the different groups. We validated our findings in the DETECT cohort. Results: Between 2005 and March 2019, 268 RHCs were performed in this single-centre cohort. Using the prior definition, 137 (51%) were diagnosed with PH, with 89 classified as pre-capillary PH (56 with PAH and 33 with PH due to lung disease and/or hypoxia), 29 as post-capillary PH, and 19 as combined pre- and post-capillary PH. When the updated definition was applied to the cohort, seven out of 131 (5%) with no PH were reclassified to pre-capillary PH (PAH (n=1), PH due to lung disease (n=3) and post-capillary PH (n=3)). In those with mPAP 21–24 mmHg, with no left heart or significant lung disease, one out of 28 (4%) in our cohort and four out of 36 (11%) in the DETECT cohort were reclassified as PAH. Conclusion: The updated PH definition does not appear to have a significant impact on the diagnosis of PH in two different screening cohorts. In two screening cohorts of scleroderma spectrum disorders, the proposed 6th World Symposium on Pulmonary Hypertension definition does not appear to have a great impact on the reclassification of patients with PAH http://bit.ly/2WKbGMT